2023
DOI: 10.3390/s23167190
|View full text |Cite
|
Sign up to set email alerts
|

UAV-YOLOv8: A Small-Object-Detection Model Based on Improved YOLOv8 for UAV Aerial Photography Scenarios

Abstract: Unmanned aerial vehicle (UAV) object detection plays a crucial role in civil, commercial, and military domains. However, the high proportion of small objects in UAV images and the limited platform resources lead to the low accuracy of most of the existing detection models embedded in UAVs, and it is difficult to strike a good balance between detection performance and resource consumption. To alleviate the above problems, we optimize YOLOv8 and propose an object detection model based on UAV aerial photography s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(44 citation statements)
references
References 59 publications
(68 reference statements)
1
20
0
Order By: Relevance
“…The ERGW-net consists of a backbone, neck, and head. The backbone leverages modified CSPDarknet53 [29] with a new block called iRepblock, which combines the advantages of InceptionNet [30] and ResNet [31] to improve feature acquisition while decreasing computational demands. The neck fuses and categorizes the infrared image features, and a new loss function is provided at the head to improve the network's ability to process small road objects from aerial infrared images.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERGW-net consists of a backbone, neck, and head. The backbone leverages modified CSPDarknet53 [29] with a new block called iRepblock, which combines the advantages of InceptionNet [30] and ResNet [31] to improve feature acquisition while decreasing computational demands. The neck fuses and categorizes the infrared image features, and a new loss function is provided at the head to improve the network's ability to process small road objects from aerial infrared images.…”
Section: Methodsmentioning
confidence: 99%
“…The role of the backbone is to extract features from images. To improve the overall performance of the backbone, we propose a new Rep-style backbone structure based on modified CSPDarknet53 [29] from YOLOv8. In other words, we provide a Rep-style capability that supports the modified CSPDarknet53 by orchestrating ResNet, InceptionNet, and efficient RepVGG ConvNet capabilities [32].…”
Section: Backbonementioning
confidence: 99%
“…The improved YOLOv8 network [16] incorporates the characteristics of small target objects in real-world scenarios by introducing blur and noise operations. Subsequently, the network introduces the Asymptotic Feature Pyramid Network (AFPN) [17] to highlight the impact of key layer features after feature fusion, addressing direct interaction issues between non-adjacent layers.UAV-YOLOv8 [18] has optimized YOLOv8 in several aspects. Firstly, it adopts Wise-IoU (WIoU) [19] v3 as the bounding box regression loss and employs a judicious gradient assignment strategy to focus the model more on samples with common quality, thereby improving the model's localization capability.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, processing the context region of targets instead of simple pixel-by-pixel processing during training [24] yields an efficient multi-scale training approach. Another study [25] has demonstrated improved detection performance through the utilization of relevant information across different feature maps.…”
Section: Related Workmentioning
confidence: 99%